Stochastic partial budget analysis of strategies to reduce the prevalence of lung lesions in finishing pigs at slaughter - Jerlström, Josefine; Huang, Wei; Ehlorsson, Carl-Johan; Eriksson, Ingvar; Reneby, Amanda; Comin, Arianna (Frontiers in Veterinary Science, 2022)
Ante- and post-mortem inspections of food-producing animals at slaughter are mandatory activities carried out in many countries to ensure public health, animal health and meat quality. In finishing pigs, lung lesions are the most frequent defects found in meat inspections. It is possible to implement managerial strategies on-farm to reduce the occurrence and spread of respiratory diseases, but such strategies come with additional costs that could impede implementation. This study assessed the economic impact of two strategies aimed at reducing the prevalence of lung lesions in finishing pigs at slaughter by improving the health conditions of the animals during the production cycle. First, a farrow-to-finish pig farm with 355 sows was modelled based on the current standard practice for finishing pig production in Sweden, using economic data, meat inspection data and biological variables from the literature and expert opinions. Partial budget analysis was then performed in which the baseline-farm was compared with two hypothetical strategies aimed at reducing the occurrence and spread of respiratory diseases during pig production: S1) avoiding mixing of litters after weaning and S2) keeping purchased pregnant gilts separated from sows during gestation, farrowing and lactation. Both these strategies intended to reduce the occurrence of respiratory disease in finishing pigs at slaughter gave an average gain in yearly annual net income (33,805 SEK in S1 and 173,160 SEK in S2, equal to 3,146 € and 16,113 €, respectively), indicating that both were economically sustainable under the assumed conditions. Impact analysis of the two strategies revealed that the reduced prevalence of lung lesions when adopting one of the strategies was the most influential factor in net benefit change on-farm. Overall, the results suggest that with increasing prevalence of lung lesions in Swedish pig production (as also observed worldwide in recent years), adopting an effective strategy to decrease respiratory infections will become more relevant and more economically beneficial.